Fixing roller, resin composition for fixing roller base material layer, and method for manufacturing fixing roller
Patent Information
- Application Number
- JP2023132643
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-28
AI Technical Summary
【0009】 [本開示の効果] 本開示の一態様に係る定着ローラは、基材層の端部の耐摩耗性に優れる。
Smart Images

Figure 2025027659000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a fixation roller, a resin composition for a fixation roller base layer, and a method for producing a fixation roller. [Background technology]
[0002] In image forming devices such as copiers and laser beam printers, a thermal fixing method is generally adopted in the final stage of printing and copying. This thermal fixing method is a method in which an image is formed by passing a transfer target, such as a printing paper to which a toner image has been transferred, between a fixing roller, which has a heat source on its inner circumferential surface, and a pressure roller, thereby heating and melting the unfixed toner and fixing the toner to the transfer target.
[0003] The fixing roller has a structure in which a tubular core body made of polyimide is used as a base layer from the viewpoint of moldability. This polyimide tubular body is easily worn and generates wear debris due to sliding contact with a nip plate provided in the inner peripheral surface. Furthermore, the wear debris of polyimide may aggregate together and become large lumps, accelerating wear. In addition, when a polyimide tubular body is used, the torque may increase due to the high friction coefficient. In response to these problems, a film tubular body for a fixing device using polyimide with added lubricant has been disclosed (see JP 2001-56615 A). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2001-56615 A Summary of the Invention
[0005] The fixing roller of the present disclosure includes a cylindrical substrate layer containing graphite, a plate-like filler, and polyimide as a main component, and the plate-like filler has a Mohs hardness of 5 or more. [Brief description of the drawings]
[0006] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a fixing roller according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] [Problem that this disclosure aims to solve] Conventionally, in image forming devices, slight vibration occurs during paper transport, and the printer housing and the end of the fixing roller are likely to come into contact. When the end of the base layer of the fixing roller and the printer housing come into contact with each other, wear occurs at the end of the base layer of the fixing roller, and the strength of the fixing roller can be improved. In particular, the fixing roller is heated to a high temperature during fixing operation, which accelerates the decrease in strength and makes damage more likely to occur. For this reason, there is a demand for the fixing roller to have improved wear resistance.
[0008] An object of the present disclosure is to provide a fixing roller having excellent wear resistance at the ends of a base layer.
[0009] [Effects of this disclosure] The fixing roller according to one aspect of the present disclosure has excellent wear resistance at the end portion of the base layer.
[0010] [Description of the embodiments of the present disclosure] First, the embodiments of the present disclosure will be listed and described.
[0011] The fixing roller of the present disclosure is (1) The conductive paste has a cylindrical substrate layer containing graphite, a plate-like filler, and a polyimide as a main component, and the plate-like filler has a Mohs hardness of 5 or more.
[0012] The fixing roller includes a base layer mainly composed of polyimide, so that the friction coefficient of the base layer can be reduced while maintaining the characteristics of the polyimide base material, which has good moldability. In addition, the base layer contains a plate-like filler having a Mohs hardness of 5 or more, so that the wear resistance of the fixing roller can be further improved. In addition, the base layer contains graphite, so that the thermal conductivity of the fixing roller can be effectively improved, and the temperature of the end of the base layer is less likely to rise. Therefore, in the fixing roller, the strength reduction of the end of the base layer due to the temperature rise is suppressed, so that the end is less likely to be damaged even if the end of the base layer of the fixing roller comes into contact with the printer housing. Therefore, the fixing roller has excellent wear resistance of the end of the base layer. In this disclosure, the term "roller" refers to a concept including a sleeve-shaped or endless belt-shaped roller that can change the shape of a cross section perpendicular to the axial direction.
[0013] The "major component" is the component with the highest content, for example, a component with a content of 57% by volume or more. "Mohs hardness" is a hardness index expressed on a 10-point scale, and is a value obtained by rubbing the corresponding standard substance with the substance to be measured and evaluating the hardness relative to the standard substance based on whether or not it is scratched. The standard substances are, in order from soft (Mohs hardness 1) to hard (Mohs hardness 10), 1: talc, 2: gypsum, 3: calcite, 4: fluorite, 5: apatite, 6: feldspar, 7: quartz, 8: topaz, 9: corundum, and 10: diamond. The Mohs hardness is measured by preparing two smooth plates with known Mohs hardness, placing the foreign object to be measured between the two plates, and rubbing the two plates together to check for scratches on the plate surface. The term "plate-like" refers to a shape that is thin relative to the area of the plate surface, and may be, for example, plate-like, thin-flaky, scaly, or flake-like. In addition, "plate-like" includes, for example, a case in which the surface is uneven or has steps (such as a wave shape) in the thickness direction, either naturally or during processing.
[0014] The aspect ratio of the front or back surface of the plate-like body in plan view is preferably 0.2 or more, more preferably 0.3 or more. Here, the "aspect ratio" is the ratio of the long diameter (major axis diameter) a of the particle to the short diameter (minor axis diameter) b of the particle. In other words, the aspect ratio is b / a. Here, when a particle is thrown onto a horizontal plane and observed in a direction perpendicular to the plane in the state in which the particle is most stable, the smallest distance between two parallel lines tangent to the outline (projected image) of the particle is defined as the short diameter b, and the distance measured in a direction perpendicular to the short diameter is defined as the long diameter a. The short diameter b and the long diameter a refer to the average thickness measured at ten arbitrary points on the particle.
[0015] (2) In the above (1), the platy filler may have a Mohs hardness of at least 6. When the platy filler has a Mohs hardness of at least 6, the abrasion resistance of the end portion of the base layer can be further improved.
[0016] (3) The resin composition for the fixation roller base layer of the present disclosure contains graphite, a plate-like filler, an organic solvent, and a polyimide precursor as a main component, and the plate-like filler has a Mohs hardness of 5 or more. Since the resin composition for the fixation roller base layer contains a polyimide precursor as a main component, it is possible to form a fixation roller base layer that can obtain a reduction effect of the friction coefficient of the base layer while maintaining the characteristics of the polyimide base material having good moldability. In addition, by containing a plate-like filler having a Mohs hardness of 5 or more, the abrasion resistance of the formed base layer can be improved. By containing graphite, the thermal conductivity of the formed base layer can be effectively improved, and the temperature of the end of the base layer is unlikely to increase. As a result, the resin composition for the fixation roller base layer can form a base layer that can suppress the decrease in strength of the end due to the temperature increase, so that even if the end of the base layer of the fixation roller comes into contact with the printer housing, the end of the base layer can be suppressed from being damaged. Therefore, according to the resin composition for the fixation roller base layer, a base layer having excellent abrasion resistance of the end of the base layer can be formed.
[0017] (4) The method for manufacturing a fixing roller according to the present disclosure includes a step of producing a cylindrical substrate layer containing graphite, a plate-like filler, and polyimide as a main component, and the plate-like filler has a Mohs hardness of 5 or more.
[0018] The manufacturing method of the fixing roller produces a base layer mainly composed of polyimide, and thus the effect of reducing the coefficient of friction of the fixing roller can be obtained while maintaining the characteristics of the polyimide base material with good moldability. Furthermore, by producing a base layer containing a plate-like filler having a Mohs hardness of 5 or more, the wear resistance of the fixing roller can be improved. Furthermore, by producing a base layer containing graphite, the thermal conductivity of the base layer can be effectively improved, and the temperature of the end of the base layer is unlikely to increase. Therefore, the manufacturing method of the fixing roller can produce a fixing roller having a base layer in which the strength reduction of the end of the base layer due to temperature increase is suppressed. Therefore, according to the manufacturing method of the fixing roller, a fixing roller having excellent wear resistance of the end of the base layer can be reliably produced.
[0019] [Details of the embodiment of the present disclosure] Hereinafter, a fixing roller according to an embodiment of the present disclosure will be described in detail with reference to the drawings.
[0020] <Fuser roller> The fixing roller according to the present embodiment includes a cylindrical base layer. The fixing roller may further include an outermost layer that is laminated directly or indirectly on the outer peripheral surface of the base layer and is mainly composed of fluororesin. FIG. 1 is a schematic cross-sectional view showing the fixing roller 1 according to the present embodiment. The fixing roller 1 includes a cylindrical base layer 2 and an outermost layer 4 that is laminated on the outer peripheral surface of the base layer 2 and is mainly composed of fluororesin. Since the fixing roller 1 has a cylindrical shape, it can be suitably used as a fixing roller in a fixing unit of an image forming device such as a copier, a printer, or a facsimile.
[0021] The lower limit of the average thickness of the fixing roller 1 is not particularly limited, but may be, for example, 20 μm, and the upper limit of the average thickness may be, for example, 300 μm. Here, the "average thickness" refers to the average value of thicknesses measured at any ten points.
[0022] [Base material layer] The base layer 2 has a cylindrical shape and can be suitably used for various rotating bodies (rollers) of image forming devices.
[0023] The average thickness of the base layer 2 is not particularly limited as long as sufficient strength can be maintained, and may be, for example, 10 μm or more and 150 μm or less.
[0024] (Polyimide) The base layer 2 is mainly composed of polyimide. The polyimide is relatively light and has excellent heat resistance and flexibility. The base layer 2 is mainly composed of polyimide, which improves moldability. Polyimide is a resin having an imide bond in the molecule. Polyimide can be obtained, for example, by polycondensing tetracarboxylic acid or its anhydride as an acid component and diamine compound as an amine component in a reaction solvent, and dehydrating and ring-closing the obtained polyimide precursor by heating or the like.
[0025] Examples of the tetracarboxylic acid or anhydride thereof include pyromellitic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, benzene-1,2,3,4-tetracarboxylic dianhydride, naphthalene-2,3,6,7-tetracarboxylic dianhydride, 3,3',4,4'-diphenyltetracarboxylic dianhydride, 2,2'',3,3''-p-terphenyltetracarboxylic dianhydride, 2,2-bis(2,3-dicarboxyphenyl)-propane dianhydride, bis(2,3-dicarboxyphenyl)ether dianhydride, bis(2,3-dicarboxyphenyl)ether dianhydride, and bis(2,3-dicarboxyphenyl)ether dianhydride. Examples of the tetracarboxylic acid dianhydride include aromatic tetracarboxylic acid dianhydrides such as bis(2,3-dicarboxyphenyl)methane dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic acid dianhydride, bis(2,3-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, perylene-3,4,9,10-tetracarboxylic acid dianhydride, and phenanthrene-1,2,7,8-tetracarboxylic acid dianhydride, alicyclic acid anhydrides such as cyclopentane-1,2,3,4-tetracarboxylic acid dianhydride, and heterocyclic derivatives such as pyrazine-2,3,5,6-tetracarboxylic acid dianhydride. The above tetracarboxylic acids or anhydrides can be used alone or in combination of two or more.
[0026] Examples of the diamine compound include aromatic diamines such as 2,2-di(p-aminophenyl)-6,6'-bisbenzoxazole, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylpropane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenylsulfone, 4,4'-diaminodiphenylether, benzidine, 4,4'-diamino-p-terphenyl, p-bis(2-methyl-4-aminopentyl)benzene, 1,5-diaminonaphthalene, 2,4-diaminotoluene, m-xylene-2,5-diamine, and m-xylylenediamine, and aliphatic diamines such as piperazine, methylenediamine, ethylenediamine, and tetramethylenediamine. The diamine compounds can be used alone or in combination of two or more.
[0027] The lower limit of the polyimide content in the base layer 2 may be 57% by volume or 80% by volume. When the content is equal to or greater than the lower limit, the flexibility and heat resistance of the fixing roller 1 can be improved. The upper limit of the polyimide content in the base layer 2 may be 92.1% by volume. When the content is equal to or less than the upper limit, the content of graphite and plate-like filler in the base layer 2 can be sufficiently ensured.
[0028] (graphite) The base layer 2 contains graphite. The base layer 2 contains graphite, which can improve the thermal conductivity of the fixing roller. Examples of graphite include natural graphite.
[0029] The lower limit of the average particle size of graphite may be 1 μm or 3 μm. Meanwhile, the upper limit of the average particle size of graphite may be 30 μm or 20 μm. When the average particle size of graphite is equal to or less than the above lower limit, the thermal conductivity of the base layer 2 can be made sufficient. Meanwhile, when the average particle size of graphite is equal to or less than the above upper limit, the dispersibility of graphite is increased, thereby improving the wear resistance and moldability of the end of the base layer 2, and the smoothness of the surface of the base layer 2. The term "average particle size" refers to a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50%, based on the particle size distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).
[0030] The lower limit of the graphite content in the base layer 2 may be 7 volume % or 10 volume %. Meanwhile, the upper limit of the graphite content in the base layer 2 may be 35 volume % or 32 volume %. When the graphite content in the base layer 2 is equal to or greater than the above lower limit, the thermal conductivity of the base layer 2 can be made sufficient. Meanwhile, when the graphite content in the base layer 2 is equal to or less than the above upper limit, the abrasion resistance and mechanical strength of the end portion of the base layer 2 can be made sufficient.
[0031] (Plate-shaped filler) The base layer 2 contains a flake-like filler. When the base layer 2 contains a flake-like filler, the abrasion resistance of the fixing roller 1 can be improved.
[0032] The Mohs hardness of the flake-like filler is not less than 5, may be not less than 6, or may be not less than 7. When the flake-like filler has a Mohs hardness of not less than 5, the end portion of the base layer 2 can have good abrasion resistance.
[0033] As the plate-like filler, known ones can be used, for example, alumina (Mohs hardness 8 to 9), glass (Mohs hardness 6 to 7), and titanium oxide anatase type (Mohs hardness 5 to 6). A plurality of types of the plate-like filler can be used.
[0034] The lower limit of the average particle size of the plate-like filler may be 1 μm or 3 μm. Meanwhile, the upper limit of the average particle size of the plate-like filler may be 30 μm or 20 μm. When the average particle size of the plate-like filler is 1 μm or more, the wear resistance of the end of the base layer 2 can be made sufficient. Meanwhile, when the average particle size of the plate-like filler is 30 μm or less, the dispersibility of the plate-like filler is increased, and the moldability of the base layer 2 and the smoothness of the surface of the base layer 2 can be improved.
[0035] The content of the platy filler having a Mohs hardness of 5 or more and less than 6 in the base layer 2 may be 4 vol% or more and 8 vol% or less. The content of the platy filler having a Mohs hardness of 6 or more and less than 8 in the base layer 2 may be 0.3 vol% or more and 8 vol% or less. The content of the platy filler having a Mohs hardness of 8 or more in the base layer 2 may be 0.1 vol% or more and 8 vol% or less. When the content of the platy filler in the base layer 2 is equal to or more than the above lower limit, the abrasion resistance of the end portion of the base layer 2 can be made sufficient. On the other hand, when the content of the platy filler in the base layer 2 is equal to or less than the above upper limit, the formation of the base layer 2 can be made good.
[0036] The base layer 2 may contain other resins, fillers, and any additives as long as the effects of the present disclosure are not impaired.
[0037] (outermost layer) The fixing roller 1 may have an outermost layer 4. The outermost layer 4 is mainly composed of a fluororesin. Since the outermost layer 4 is mainly composed of a fluororesin, it has excellent abrasion resistance. Furthermore, by providing the outermost layer 4, the fixing roller 1 is given releasability, and the toner on the transfer material can be prevented from adhering to the fixing roller surface. The fluororesin is preferably one having excellent heat resistance, such as polytetrafluoroethylene (PTFE), polytetrafluoroethylene-perfluoroalkylvinylether copolymer (PFA), and tetrafluoroethylene-hexafluoropropylene copolymer (FEP). The fluororesins may be used alone or in combination of two or more. The fluororesins may contain structural units derived from other copolymerizable monomers within a range that does not impair the effects of the present disclosure.
[0038] The lower limit of the average thickness of the outermost layer 4 may be 5 μm or 20 μm. On the other hand, the upper limit of the average thickness may be 50 μm or 40 μm. When the average thickness is 5 μm or more, the durability of the fixing roller 1 can be improved. On the other hand, when the average thickness is 50 μm or less, the elasticity of the fixing roller 1 can be improved.
[0039] The outermost layer 4 may contain other resins, fillers, and any additives as long as the effects of the present disclosure are not impaired.
[0040] According to this fixing roller, the end portion of the base layer has excellent wear resistance.
[0041] <Resin composition for fixing roller base layer> The resin composition for the fixing roller base layer (hereinafter also referred to as "the resin composition for the base layer") contains graphite, a plate-like filler, an organic solvent, and a polyimide precursor as a main component. The plate-like filler has a Mohs hardness of 5 or more. Details of the graphite and the plate-like filler are as described above, so a description thereof will be omitted.
[0042] As the organic solvent, for example, aprotic polar organic solvents such as N-methyl-2-pyrrolidone (NMP), N,N-dimethylacetamide (DMAc), N,N-dimethylformamide, dimethylsulfoxide, and γ-butyrolactone can be used. These organic solvents may be used alone or in combination of two or more. The term "aprotic polar organic solvent" refers to a polar organic solvent that does not have a group that releases a proton.
[0043] The polyimide precursor is a reaction product that can be obtained by a polymerization condensation reaction between a tetracarboxylic acid or its anhydride as an acid component and a diamine compound as an amine component. The polymerization condensation reaction can be carried out in the same manner as in the synthesis of conventional polyimide precursors. A specific method for the polymerization condensation reaction is, for example, a method in which a tetracarboxylic acid or its anhydride and a diamine compound are mixed in an organic solvent. By this method, the tetracarboxylic acid or its anhydride and the diamine compound are polymerized, and a solution in which the polyimide precursor is dissolved in an organic solvent can be obtained. For example, the polymerization condensation reaction can be carried out in the presence of a reaction inhibitor to control the degree of polymerization (weight average molecular weight).
[0044] The lower limit of the graphite content in the resin composition for the base layer may be 7 volume % or 10 volume %. Meanwhile, the upper limit of the graphite content in the resin composition for the base layer may be 35 volume % or 32 volume %. When the graphite content in the resin composition for the base layer is equal to or greater than the lower limit, the thermal conductivity of the base layer formed can be sufficient. Meanwhile, when the graphite content in the resin composition for the base layer is equal to or less than the upper limit, the abrasion resistance and mechanical strength of the end of the base layer formed can be sufficient.
[0045] The content of the plate-like filler having a Mohs hardness of 5 or more and less than 6 in the resin composition for the base layer may be 4 vol% or more and 8 vol% or less. The content of the plate-like filler having a Mohs hardness of 6 or more and less than 8 in the resin composition for the base layer may be 0.3 vol% or more and 8 vol% or less. The content of the plate-like filler having a Mohs hardness of 8 or more in the resin composition for the base layer may be 0.1 vol% or more and 8 vol% or less. When the content of the plate-like filler in the resin composition for the base layer is equal to or more than the lower limit, the end of the base layer formed can have sufficient abrasion resistance. On the other hand, when the content of the plate-like filler in the resin composition for the base layer is equal to or less than the upper limit, the base layer can be well formed.
[0046] A dispersant may be added to the resin composition for the base layer. The dispersant is not particularly limited as long as it enhances the dispersibility of the graphite and the plate-like filler, and for example, a surfactant may be used. The lower limit of the amount of the dispersant added to the graphite and the plate-like filler may be 0.01% by mass or 0.3% by mass. Meanwhile, the upper limit of the amount of the dispersant added to the graphite and the plate-like filler may be 20% by mass or 10% by mass. When the amount of the dispersant added is equal to or greater than the lower limit, the dispersibility of the graphite and the plate-like filler can be improved. Meanwhile, when the amount of the dispersant added is equal to or less than the upper limit, the decrease in the mechanical strength of the base layer can be suppressed.
[0047] The upper limit of the viscosity of the resin composition for the base layer at 20°C may be 1500 Pa·s or 300 Pa·s. Meanwhile, the lower limit of the viscosity of the resin composition for the base layer at 20°C may be 10 Pa·s. When the viscosity of the resin composition for the base layer at 20°C is equal to or less than the upper limit, the occurrence of unevenness in the base layer obtained by coating the resin composition for the base layer can be suppressed. Meanwhile, when the viscosity of the resin composition for the base layer at 20°C is equal to or more than the lower limit, the occurrence of dripping or repellency during coating or curing of the resin composition for the base layer can be suppressed.
[0048] According to the resin composition for a base layer of a fixing roller, a base layer having excellent abrasion resistance at the ends of the base layer can be formed.
[0049] <Method of Manufacturing Fixing Roller> The manufacturing method of the fixing roller includes a step of preparing a cylindrical base layer containing graphite, a plate-like filler, and a polyimide as a main component. The step of preparing the base layer includes, for example, a step of applying a resin composition for the base layer to a cylindrical or cylindrical core, a step of curing the applied resin composition for the base layer, and a step of demolding the base layer from the core. The manufacturing method of the fixing roller may further include a step of laminating an outermost layer mainly composed of a fluororesin directly or indirectly on the outer peripheral surface of the base layer.
[0050] [Process for producing base layer] (Coating process) In this step, a resin composition for forming a base layer is applied to a columnar or cylindrical core body, and the base layer is laminated. When the core body is a columnar core body, the resin composition for forming the base layer is applied to the outer peripheral surface of the columnar core body, and when the core body is a cylindrical core body, the resin composition for forming the base layer is applied to the outer peripheral surface or inner peripheral surface of the cylindrical core body.
[0051] The surface of the core body coated with the resin composition for the base layer may be coated with a release agent such as silicone oil or with a ceramic coating, which may be silica, alumina, zirconia, silicon nitride, etc. coated by a sol-gel method, alumina, zirconia, etc. coated by a thermal spraying method, or aluminum nitride, etc. coated by a sputtering method.
[0052] The resin composition for the base layer contains a polyimide precursor for forming the polyimide of the base layer, graphite, a flake-like filler, and an organic solvent. The details of the resin composition for the base layer are as described above, and therefore the overlapping description will be omitted.
[0053] As a specific coating method of the resin composition for the base layer, for example, a method of coating using a dispenser is preferably used, in which the core body is rotated about its axis, and the resin composition for the base layer is continuously coated on the outer or inner peripheral surface of the core body while the nozzle of the dispenser is moved relatively in the axial direction of the core body.
[0054] It is preferable that the nozzle of the dispenser is brought into contact with the outer or inner peripheral surface of the core. Furthermore, the moving speed V (mm / s) of the nozzle of the dispenser in the axial direction of the core and the rotation speed R (s -1 ) may be less than 3 or less than 1.5. By adjusting the movement speed of the nozzle of the dispenser and the rotation speed of the core in this manner, the resin composition for the base layer is effectively stirred in the vicinity of the nozzle, and the occurrence of striped patterns due to the coating path and unevenness in the base layer can be prevented.
[0055] The nozzle of the dispenser may be a synthetic resin tube, a rubber tube, a metal tube, etc. Among these, from the viewpoint of rigidity and prevention of damage to the core surface, a tube mainly composed of polytetrafluoroethylene or a polytetrafluoroethylene-perfluoroalkyl vinyl ether copolymer may be used.
[0056] (Hardening process) In this step, the resin composition for the base layer applied to the core is cured to form the base layer. Specifically, the resin composition for the base layer can be cured by heating. The polyimide precursor in the resin composition for the base layer is imidized by heating, and a tubular base layer is formed.
[0057] (De-molding process) In this step, the base layer formed in the curing step is removed from the core.
[0058] [Step of laminating the outermost layer] In this step, an outermost layer mainly composed of a fluororesin is laminated directly or indirectly on the outer peripheral surface of the substrate layer. Examples of the lamination method include a method of applying a resin composition for the outermost layer containing a fluororesin to the outer peripheral surface of the substrate layer and baking the composition, and a method of covering the substrate layer with a fluororesin tube and heat shrinking the layer. When the outermost layer is laminated on the outer peripheral surface of the substrate layer via an adhesive, the adhesive is applied to the outer peripheral surface of the substrate layer or the inner peripheral surface of the fluororesin tube, and then the outermost layer is laminated by the above-mentioned method.
[0059] The step of laminating the outermost layer may be carried out before the step of demolding. Furthermore, the curing step may be carried out by heating after coating the resin composition for the outermost layer or covering with the fluororesin tube. That is, after coating the resin composition for the base layer on the core, the solvent of the resin composition for the base layer is dried and removed, and then the resin composition for the outermost layer is coated or the fluororesin tube is covered. Finally, the polyimide precursor may be imidized and the fluororesin may be baked or shrunk simultaneously by heating.
[0060] According to this method for manufacturing a fixing roller, a fixing roller having excellent wear resistance at the end portion of the base layer can be reliably manufactured.
[0061] [Other embodiments] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is not limited to the configurations of the above-described embodiments, but is indicated by the claims, and is intended to include all modifications within the meaning and scope of the claims.
[0062] In the above embodiment, the fixing roller includes the base layer and the outermost layer, but it may include other layers between the outermost layer and the base layer, such as a primer layer and an elastic layer.
[0063] The inner peripheral surface of the outermost layer may be subjected to a surface treatment to improve adhesion, for example, roughening by plasma treatment, liquid ammonia treatment, corona treatment, tetra-etch treatment, laser etching treatment, etc.
[0064] The abrasion resistance of the outermost layer may be improved by irradiating the outermost layer with ionizing radiation to crosslink the fluororesin. EXAMPLES
[0065] The present disclosure will be described more specifically below with reference to examples, but the present disclosure is not limited to the following examples.
[0066] <Base layer No. 1 to No. 27> First, a resin composition for base layer, which is a coating liquid, was prepared by blending graphite and a filler in the content ratios shown in Table 1 into a resin composition for base layer containing a polyimide precursor. Table 1 also shows the shape, average particle size, Mohs hardness, and aspect ratio of the graphite and each filler. The following materials were used for the resin composition for the base layer. (1) Polyimide: "JIV-1002HS" manufactured by JFE Chemical Corporation (2) Plate graphite: "FS-15" manufactured by Fuji Graphite Industries Co., Ltd. (3) Fibrous graphite: "VGCF-H" manufactured by Resonac (4) Glass: Nippon Sheet Glass Co., Ltd. "MXG015FYX" (5) Glass: Nippon Sheet Glass Co., Ltd. "RCF-015" (6) Alumina: DIC "AP20" (7) Alumina: DIC "AP05" (8) Titanium oxide (anatase type): Ishihara Sangyo Kaisha, Ltd. "MPT-350" (9) Polytetrafluoroethylene (PTFE): Mitsui-Chemours Fluoroproducts "MP-1300J" (10) Boron nitride: Momentive "PT100" (11) Titanium oxide (rutile type): Ishihara Sangyo Kaisha, Ltd. "FTL-300"
[0067] Next, a cylindrical core body with an outer diameter of 20 mm, the outer peripheral surface of which was coated with ceramics, was prepared, and the coating liquid was applied to the outer peripheral surface of this cylindrical core body. Specifically, the nozzle of a dispenser was brought into contact with the outer peripheral surface of the cylindrical core body, and the cylindrical core body was rotated while the nozzle was moved at a constant speed in the axial direction of the cylindrical core body, and the coating liquid was supplied from the nozzle of the dispenser to the outer peripheral surface of the cylindrical core body in a fixed amount. A tube with an inner diameter of 6 mm was used as the nozzle of the dispenser. The nozzle was moved from a position (supply start position) 20 mm from one end of the cylindrical core body to a position (supply stop position) 20 mm from the other end. After the coating of the coating liquid, the cylindrical core body was heated stepwise to 400°C while rotating, and after cooling, the solidified substrate layer was demolded from the cylindrical core body to obtain substrate layers No. 1 to No. 27. The average thickness of the substrate layer was 60 μm.
[0068] [evaluation] Next, the end wear amount [mm] and thermal conductivity [W / mK] were evaluated for base layers No. 1 to No. 27.
[0069] (Amount of edge wear and grinding) The amount of wear and abrasion at the end portion was evaluated according to the following procedure. First, one end of the base layer was attached to the turntable of the planetary grinder, and the other end was attached to a grinding disk with #3000 abrasive paper. A load of 200 g was applied from above the grinding disk, and the planetary grinder was rotated at 200 rpm for 600 seconds to grind the other end of the base layer with the grinding disk. The value obtained by subtracting the total length of the base layer after grinding from the total length of the base layer before grinding was taken as the end wear grinding amount.
[0070] (Thermal Conductivity) The thermal conductivity was evaluated according to the following procedure. The thermal diffusivity in the thickness direction of the base layer was measured by temperature wave thermal analysis in accordance with ISO22007-3:2008 using an ai-Phase "M3 Type1". The specific heat of the base layer was then measured by DSC in accordance with JIS-K7123:2012 using a Hitachi High-Tech Science "DSC7020". The density of the base layer was then measured by the water displacement method in accordance with JIS-K7112:1999 using an A&D "BM-200" and a Mettler Toledo "Specific Gravity Measurement Kit". The thermal conductivity was calculated from the product of the thermal diffusivity, specific heat and density.
[0071] Table 1 shows the evaluation results of the edge wear amount and thermal conductivity of films No. 1 to No. 27.
[0072] [Table 1]
[0073] [Table 2]
[0074] As shown in Table 1, Test Nos. 1 to 20, which have a base layer containing graphite, a plate-like filler, and polyimide as the main component, and in which the plate-like filler has a Mohs hardness of 5 or more, had good thermal conductivity and low edge abrasion. When the plate-like filler had a Mohs hardness of 6 or more, the edge abrasion was further reduced. In particular, Test Nos. 8 to 10, which contain 15 volume % plate-like graphite and 1 volume % to 5 volume % alumina with a large Mohs hardness and average particle size, had low edge abrasion.
[0075] On the other hand, as shown in Table 2, Tests No. 21, No. 22 and No. 27, which did not contain plate-like filler, Tests No. 23 and No. 24, which contained plate-like filler with a Mohs hardness of less than 5, and Tests No. 25 and No. 26, which contained needle-like filler, had a large amount of edge wear and abrasion regardless of the thermal conductivity value.
[0076] The above results show that the fixing roller has excellent wear resistance at the end portion of the base layer. [Explanation of symbols]
[0077] 1 Fuser roller 2 Base material layer 4 Outermost layer
Claims
1. A cylindrical substrate layer containing graphite, a plate-like filler, and polyimide as a main component is provided, The plate-like filler has a Mohs hardness of 5 or more.
2. 2. The fixing roller according to claim 1, wherein the plate-like filler has a Mohs hardness of 6 or more.
3. It contains graphite, a plate-like filler, an organic solvent, and a polyimide precursor as the main component, The resin composition for a fixing roller base layer, wherein the plate-like filler has a Mohs hardness of 5 or more.
4. The method includes a step of preparing a cylindrical base layer containing graphite, a plate-like filler, and polyimide as a main component, The method for producing a fixing roller, wherein the plate-like filler has a Mohs hardness of 5 or more.
Citation Information
Patent Citations
Fixing device and film tube for fixing device
JP2001056615A